Limits and problems of European integration. The conference of May 30 - June 2, 1961. Papers by E.B. Haas, D. Mitrany, [M.] van der Goes van Naters [a.o.]. With an introd. by B. Landheer (Nijhoff, 1963)
Stichting Grotius Seminarium.